Development of E-Modul Based on a Problem Based Learning Model to Improve Problem Solving Ability and Appreciation of Mathematics at SMP Dharma Pancasila Medan - suharmita, Suharmita; mulyono, Mulyono; Fauzi, Kms Amin; Suharyanisa, Suharyanisa (FKIP Universitas Muhammadiyah Tangerang, 2024)
This study aims to describe: 1) the validity, practicality and effectiveness of e-modul based on a problem-based learning model that was developed to improve problem solving abilities and appreciation mathematics of students at SMP Dharma Pancasila Medan; 2) increasing students problem-solving abilities through E-Modul based on the developed problem-based learning model; 3) increasing student appreciation of mathematics through E-Modul based on the developed problem-based learning model. This research is a developmental research using the type of ADDIE development model. This development model consists of 5 stages of development, namely Analyze, Define, Development, Implementation and Evaluation. From the results of trial I and trial II, it was obtained: 1) E-modul based on a problem-based learning model to improve students' problem-solving skills and appreciation mathematics that was developed met valid, practical and effective criteria; 2) Improvement of problem-solving skills using e-modul based on a problem-based learning model that has been developed as seen from the N-gain value in trial I of 0.36 increased to 0.40 in trial II, meaning that it is in the